Avaliação do polimorfismo do gene do fator regulador de Interferon 8 (IRF8) (rs10514611), na anemia falciforme: associação com a clínica, com biomarcadores laboratoriais e com o uso de hidroxiureia - Maia, Adriano Evangelista (2024)
Sickle cell anemia (SCA) is a genetic disease resulting from a mutation in the β-globin gene, leading to the production of hemoglobin S (HbS) and whose main complication is chronic inflammation. The IRF8 gene is associated with the immune and inflammatory response. This study aimed to determine the frequency of a polymorphism in the IRF8 gene and its relationship with clinical, laboratory parameters, and the use of hydroxyurea (HU). This was a cross-sectional, quantitative, and analytical study that included 63 patients with sickle cell anemia and 81 blood donors as a control group. Information was collected from patients' medical records, such as sociodemographic (age and sex), laboratory (complete blood count, urea, creatinine, AST, ALT, GGT, lactate dehydrogenase, reticulocyte count, serum iron, ferritin, transferrin saturation index, and iron binding capacity), and clinical complications (stroke, renal insufficiency, acute chest syndrome, leg ulcers, cholelithiasis, cholecystitis, and heart disease). The polymorphism in the IRF8 gene rs10514611 was identified using TaqMan® probes and real-time polymerase chain reaction (RT-PCR). Significant results were defined as p<0.05. Most patients were female 40 (65.6%), and the majority of them 49 (86.7%) were undergoing HU treatment. Hematological parameters showed a significant decrease in patients compared to the control group, including red blood cell count, hemoglobin, hematocrit, mean corpuscular volume, mean corpuscular hemoglobin, white blood cells, monocytes, lymphocytes, as well as reticulocytes and platelets. Genetic analysis revealed a predominance of the C allele (wild type) 105 (83.52%) and the CC genotype 42 (43.6%) in patients, and a higher presence of the C allele 141 (87%) and the CC genotype 61 (61.4%) in the control group. Hardy-Weinberg equilibrium was verified for allelic and genotypic frequencies. There were no differences in laboratory variables related to renal, hepatic function, and hemolysis, and no association with the polymorphism was found with the analyzed clinical complications, regardless of HU use. The absence of difference was also observed in the group of patients who did not use HU. It is concluded that the frequency of the IRF8 gene rs105114611 found was similar between patients and the control group and that this polymorphism does not impact clinical and biochemical alterations in patients with sickle cell anemia who use HU, as well as those who do not use it.